2002
DOI: 10.1097/00001721-200212000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Two antiprothrombin antibodies against prothrombin and prothrombin–phosphatidyl serine show partial but not total identity

Abstract: Recently, an enzyme-linked immunosorbent assay (ELISA) using prothrombin (PT) as the antigen has become a widely used test. Two ELISA methods for the detection of antiprothrombin antibody have been used extensively: one method employs PT as an antigen (aPT), and the other employs PT and phosphatidyl serine (aPT/PS) as antigens along with Ca. However, the results obtained by the two methods are not necessarily consistent with each other even using the same samples, suggesting the possibility that aPT and aPT/PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Comparative studies gave additional indication of their diagnostic relevance and confirmed their closer correlation with APS and LA activity as compared to aPT [7, 8, 13, 30]. The protocol by Matsuda et al [12] used a higher concentration of phosphatidylserine (65  μ g/mL) and prothrombin (20  μ g/mL), while the protocols by Atsumi et al [7], Tincani et al [6], and Žigon et al [10] all used lower concentrations of phosphatidylserine (50  μ g/mL) and prothrombin (10  μ g/mL). Additional major modifications between Matsuda et al and later protocols are different times and temperatures of phosphatidylserine and prothrombin incubation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparative studies gave additional indication of their diagnostic relevance and confirmed their closer correlation with APS and LA activity as compared to aPT [7, 8, 13, 30]. The protocol by Matsuda et al [12] used a higher concentration of phosphatidylserine (65  μ g/mL) and prothrombin (20  μ g/mL), while the protocols by Atsumi et al [7], Tincani et al [6], and Žigon et al [10] all used lower concentrations of phosphatidylserine (50  μ g/mL) and prothrombin (10  μ g/mL). Additional major modifications between Matsuda et al and later protocols are different times and temperatures of phosphatidylserine and prothrombin incubation.…”
Section: Discussionmentioning
confidence: 97%
“…It was demonstrated that antibodies recognized prothrombin more efficiently in aPS/PT ELISA [11] and that aPS/PT correlated better with APS and LA activity [7, 8, 12, 13] as compared to aPT. The inclusion of aPS/PT, but not aPT, to the laboratory criteria for APS has been proposed [14].…”
Section: Introductionmentioning
confidence: 99%
“…12,15,16 Currently, it is known that aPT-A and aPS/PT are 2 different antiprothrombin antibody subpopulations with partial identity 10,11 and because our study is focused only on aPS/PT, in the present article, we only comment on previous studies performed with this antibody. Moreover, having preliminary results suggesting that aPS/PT may confirm an isolated activity of LA, we have investigated whether aPS/PT detection may be used as a second-level assay, next to the exploration of aCL and ab2GPI, to diagnose APS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown contradictory results regarding the association of antiprothrombin antibodies with thrombosis, especially VT. [5][6][7] Reviewing the literature, we notice that 2 enzyme-linked immunosorbant assay (ELISA)-based methods are commonly employed for the detection of antiprothrombin antibodies: antiprothrombin (aPT-A) assays, in which gamma-irradiated plates are coated with purified PT, or antiphosphatidylserine/prothrombin (aPS/PT) assays, in which PT is exposed to immobilized phosphatidylserine (PS). 3,8,9 Recently, it was demonstrated that antibodies detected by the aPT-A and aPS/PT assays are in fact 2 distinct populations with partial overlapping identity 10,11 as the mechanism of action of aPS/PT is mediated by increased thrombin generation. 11 Probably because the aPT-A method was the first one described, the bulk of studies on antibodies to PT were performed by means of direct antigen-binding ELISA (aPT-A).…”
Section: Introductionmentioning
confidence: 99%
“…The second ELISA uses prothrombin complexed to phosphatidylserine (aPS/PT) in the presence of calcium (Ca 2+ ) (Bevers et al, 1991;Galli et al, 1997). Some reports showing an absence of concordance between the results from the two ELISA suggest that aPT and aPS/PT could be different antibodies (Galli et al, 1997;Matsuda et al, 2002). It is worth noting that the majority of clinical studies were focused on the prevalence and the clinical significance of aPT and/or aPS/PT in systemic lupus erythematosus (Atsumi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%